Effect of smoking on visual evoked potential (VEP) and visual reaction time (VRT) - Rajbhandari Pandey, Karishma; Panday, Dipesh Raj; Limbu, Nirmala; Shah, Bhupendra; Agarwal, Kopila (Asian Journal of Medical Sciences, 2020)
Background: Nicotine in tobacco smoke causes demyelination. Again, hypoxia in long-term smokers is linked to neuropathy. Visual receptors are early sufferer of neuropathy. Visual-Acuity & other ocular tests often fail to detect subtle changes of neuropathy which, however, can be detected by VEP test. Literature review shows that changes in VEP come earlier than PFT changes in smokers. Ironically, smokers claim that smoking improves their reaction time, which can be assessed by VRT. Aims and Objective: To relate smoking status with VEP and VRT. Materials and Methods: Fifty-six subjects (smoker group = 28 & non-smoker group = 28), whose age & sex were matched, were included in the study. Their PFT, pattern VEP of both eyes & VRT were recorded. The data were compared between the two groups using unpaired t-test, considering statistical significance at p<0.05. Results: The FVC (4.35±0.83 vs. 5.32+1.18 l, p=0.022), FEF 25% (7.40+2.38 vs. 8.74+3.90 l/s, p=0.019) & FEF 50% (6.11+1.52 vs. 7.74+2.57, p= 0.010) were significantly lower in smokers compared to nonsmokers. There was no significant difference in P100 wave latency of VEP. But, VRT of smokers were significantly shorter (431.69+60.29 vs. 441.14+123.54 ms, p=0.010). Conclusion: Smokers have shorter visual reaction time and similar visual evoked potential as compared to non-smokers.